Characterisation and comparison of slow coronal hole wind intervals at 0.13au - Woolley,T; Matteini,L; Horbury,TS; Laker,R; Woodham,LD; Bale,SD; Stawarz,JE; Beri,L; McManus,MD; Badman,ST (2021)
The slow solar wind is thought to consist of a component originating close to the Heliospheric Current Sheet (HCS) in the streamer belt and a component from over-expanded coronal hole boundaries. In order to understand the roles of these contributions with different origin, it is important to separate and characterise them. By exploiting the fact that Parker Solar Probe’s fourth and fifth orbits were the same and the solar conditions were similar, we identify intervals of slow polar coronal hole wind sampled at approximately the same heliocentric distance and latitude. Here, solar wind properties are compared, highlighting typical conditions of the slow coronal hole wind closer to the Sun than ever before. We explore different properties of the plasma, including composition, spectra and microphysics, and discuss possible origins for the features that are observed.